Attitude Expressive Illocutionary Acts Found in “Asian Glow” Podcast Video - Ni Made Gita Gantari Asri; Putu Gede Budiartha (Prodi Sastra Inggris Fakultas Bahasa Asing Universitas Mahasaraswati Denpasar, 2025)
This study focuses on one specific type of expressive illocutionary acts which is attitude as found in an episode of the Asian Glow podcast. The researcher applied Searle’s (1979) theory to identify examples of attitude within expressive illocutionary acts. The attitude expressive illocutionary act typically convey negative emotional responses such as criticism, complaints, or disapproval, often directed at the listener’s behaviour or attitude. Examples include expressions like “I hate that” or “That was awful”. To analyze the meaning behind these utterances, the study also used Halliday and Hasan’s (1985) theory of context of situation. Data were gathered using an observation method combined with note-taking techniques focusing on the selected podcast episode. A descriptive qualitative approach was employed to analyze both the types of expressive illocutionary acts and their meanings within contextual settings. The findings reveal 20 data of attitude expressions found throughout the episode. In this episode, there were a lot of attitudes that found in the utterances of the podcast hosts, because as cousins, Clarence and Alcheska share an undeniable chemistry, which enhances their dynamic and makes their reactions more engaging for viewers.